Development of an efficient and eco-friendly method for mitragynine enrichment - Febriandi, Rizal; Rizaldy, Defri; Ishak, Sumail Sidik Ode; Elfahmi (Institut Teknologi Bandung, 2025)
Kratom (Mitragyna speciosa) is rich in mitragynine, a bioactive alkaloid with antinociceptive, sedative, and antimicrobial activities, and potential benefits for alleviating alcohol dependence. This study aimed to develop a safe, environmentally friendly, cost-effective, and efficient method for enriching mitragynine using macroporous resins. Extraction was performed via maceration with 70% ethanol, and the performance of macroporous resins (PAD610 and PAD900) was evaluated in terms of adsorption and desorption characteristics using UPLC-MS/MS. The results showed that the adsorption and desorption processes followed a pseudo-second-order kinetic model, indicating that mitragynine adsorption is influenced by coexisting compounds in the extract. Isothermal adsorption analysis demonstrated good agreement with the Freundlich model, with R2 values of 0.9973 for PAD610 and 0.9905 for PAD900, suggesting multilayer adsorption on heterogeneous surfaces. Under optimized conditions, macroporous resin enrichment effectively increased mitragynine content, yielding 753 mg for PAD900 and 303 mg/g for PAD610. Additionally, a flow rate of 3 BV/hour was identified as optimal for large-scale applications. This study demonstrates that macroporous resins provide an efficient and scalable approach for mitragynine enrichment from M. speciosa extract, offering a promising method for the preparation of high-purity bioactive compounds.